(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article is devoted to the study of the UK experience with the system of social and psychological rehabilitation of people with disabilities. The legislation analyzes the protection and support of people with disabilities in the UK, which enables them to maximize their potential, live a full and active life in their families, communities and society as a whole. The content of the concept of "rehabilitation", defined in normative documents, is disclosed as a personalized, interactive and collaborative process that reflects a person as a whole, enabling her to maximize their potential, to live a full and active life in their family, community, educational activities, and the workplace where it is needed. The goals of social rehabilitation of people with disabilities in the UK are considered, namely the orientation towards the person, its needs, and not the diagnosis; active involvement process, not passive care; integration of specialized and universal services; maximizing the potential of personality; work in partnership etc. The model of socio-psychological rehabilitation of people with disabilities in Great Britain, based on a multidisciplinary approach, is presented. The principles and stages of this model are described, aimed at implementation of complex, individually oriented approaches and active involvement of people with disabilities in different spheres of activity according to their needs and possibilities. The experience of British organizations that implement innovative technologies of physical, financial, informational support of people with disabilities is studied and described, in particular: the system of "contactless physiotherapy", independent personal payments, special online applications for various events of soplife, etc. The model of employment support for people with disabilities is presented in detail, which involves finding a job in accordance with the client’s capabilities, training and adaptation to the workplace, and the general support of the work program for 2 years.